PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP ANAK USIA SEKOLAH DALAM MEMILIH JAJANAN YANG AMAN DI SD MUHAMMADIYAH 16 PALEMBANG - Dian Sri Utami; Yuniza Yuniza; Sri Tirtayanti (HealthCare Nursing Journal, 2020)
Background of the research : unhealthy snacks can cause negative impact if the hygiene and safety not guaranteed. Beside it can lead to nutritional problems, the effects from unhealthy snack or food will disrupts health namely alimentary tract diseases and can cause others diseases. In fact, there are many children who have less knowledge in choosing safe snacks of food. The objective of the research : to identify the influence of health education towards knowledge an behavior of school age children in selecting safe foods at SD Muhammadiyah 16 Palembang. Methods of the research : in this study, the writer used pretest posttest control group design with total sampling technique as much as 135 students taken from class V and VI at SD Muhammadiyah 16 Palembang. Instruments used in this study were knowledge an behavior quesioner which had been modified by previous writer and they have been tested through validity and reliability test with table r score as much as 0,279. Reliablity score of knowledge quesioner were 0,754 and reliability score of behavior quesioner were 0,714. Results of the research : from wilcoxon test result there were influences on knowledge and behavior before and after conducting health education obtained p value 0,000 (p value ? 0,05). Conclusion : there are influences on health education towards knowledge and behavior of school age children in selecting safe snacks at SD Muhammadiyah 16 Palembang.